Andrej Zaliznjak. Cutting off the unnecessary - Zimmerling, Anton V. (Слово.ру: балтийский акцент, 2020)
This paper offers a polemic linguistic and philological view on the scientific heritage of one of the most prominent linguists of the 20th century, Andrej A. Zaliznjak (1935—2017), who authored fundamental works on the Russian and Old Russian languages. In different years, Zaliznjak addressed issues in morphology, syntax, accentology, and historical grammar. This apparent variety of his research interests gives an impression that Zaliznjak moved from purely structural paradigmatic descriptions to merely historical-philological analysis of specific texts. Zaliznjak basic method, however, remained unchanged throughout his life. His descriptions were always rule-based: he extracted rules from language data and tested them on a specific collection of texts. Zaliznjak’s rules can, therefore, be identified with predictive models in the sense adopted in natural sciences. His models gave accurate results since Zaliznjak had a rare gift of cutting off all kinds of redundant information in his rule-based grammatical descriptions and kept the latter apart from other linguistic issues as well as from historical-philological commentary. Although Zaliznjak himself stayed away from programmatic declarations about the language structure and avoided developing integral theories of language, he can be called a consistent structuralist who successfully applied natural science criteria to linguistic evidence.